Biological Control and Mitigation of Aflatoxin Contamination in Commodities - Ferenc Peles; Péter Sipos; Szilvia Kovács; Zoltán Győri; István Pócsi; Tünde Pusztahelyi (Toxins, 2021)
Aflatoxins (AFs) are toxic secondary metabolites produced mostly by Aspergillus species. AF contamination entering the feed and food chain has been a crucial long-term issue for veterinarians, medicals, agroindustry experts, and researchers working in this field. Although different (physical, chemical, and biological) technologies have been developed, tested, and employed to mitigate the detrimental effects of mycotoxins, including AFs, universal methods are still not available to reduce AF levels in feed and food in the last decades. Possible biological control by bacteria, yeasts, and fungi, their excretes, the role of the ruminal degradation, pre-harvest biocontrol by competitive exclusion or biofungicides, and post-harvest technologies and practices based on biological agents currently used to alleviate the toxic effects of AFs are collected in this review. Pre-harvest biocontrol technologies can give us the greatest opportunity to reduce AF production on the spot. Together with post-harvest applications of bacteria or fungal cultures, these technologies can help us strictly reduce AF contamination without synthetic chemicals.